2023
DOI: 10.47153/jbmr46.6522023
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the predictors of brand preference towards cement brands available on the South African Market: A Consumer’s Perspective

Goitumetswe Pitso,
Neo Ligaraba,
Tinashe Chuchu

Abstract: The present study examines the antecedents and outcomes of brand preference in the South African Cement Industry. Due to the unavailability of a sampling frame, non-probability sampling, a form of convenience sampling was adopted to determine suitable respondents. A self-administered questionnaire was utilised to obtain 260 valid responses from individuals identifying as customers of the South African cement industry. To analyse the data, descriptive statistics and hypotheses testing was conducted through SPSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Wahyuningsih et al (2023) discovered that brand switching happens due to product attributes and price. Pitso et al (2023) examined the brand image, price, and perceived quality as significant predictor variables of brand preference for cement brands. Liu et al (2022) found that product price has less impact on sales of high-involvement products than the product itself, whereas e-WOM awareness effects have a more significant influence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wahyuningsih et al (2023) discovered that brand switching happens due to product attributes and price. Pitso et al (2023) examined the brand image, price, and perceived quality as significant predictor variables of brand preference for cement brands. Liu et al (2022) found that product price has less impact on sales of high-involvement products than the product itself, whereas e-WOM awareness effects have a more significant influence.…”
Section: Literature Reviewmentioning
confidence: 99%